Exploring Efl Students' Preferences on Teachers’ Written Corrective Feedback in Encouraging Students' Writing Skills - Pertiwi, Octaviani Putri Pertiwi; ashadi, Ashadi (International Journal Labs, 2024)
Writing is often perceived as a challenging task, particularly for EFL (English as a Foreign Language) students who frequently struggle with confidence in their writing abilities. Although teacher feedback can be beneficial, it can sometimes exacerbate feelings of inadequacy. This study aims to explore several key areas: students' preferences for written corrective feedback (WCF), the impact of gender on these preferences, effective types of WCF to enhance learning, and how feedback can facilitate students' mastery of academic writing. The research highlights various complex skills involved in writing, such as planning, organization, coherence, and grammatical accuracy, which students often find problematic. Negative experiences with inadequate types of WCF have led to dissatisfaction among students, indicating a need for more effective feedback mechanisms. The study examines six WCF types: direct, indirect, focused, unfocused, metalinguistic, and reformulation feedback. Utilizing an explanatory mixed-method design, it combined quantitative data from a questionnaire completed by 211 English majors at two public universities in Yogyakarta, with qualitative data gathered from semi-structured interviews with four students. Analysis revealed a clear preference for direct WCF, which helps reduce confusion. A combination of direct and indirect feedback can enhance students' awareness of their writing errors. Interestingly, gender did not significantly influence WCF preferences. Ultimately, feedback tailored to students' needs, particularly through reformulation, proved to be the most effective for improving their writing skills.